2013
DOI: 10.1155/2013/567289
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Hemolytic Anemia and Nodular Lymphocyte-Predominant Hodgkin Lymphoma: A Rare Association

Abstract: Autoimmune hemolytic anemia (AIHA) has been associated with chronic lymphocytic leukemia, non-Hodgkin lymphoma, and classical Hodgkin lymphoma, but to the best of our knowledge, the association of AIHA and nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) has not been reported previously. A 20-year-old woman presented with conjunctival jaundice, fever, asthenia, and hemoglobin 9.2 g/dL revealing IgG-mediated warm antibody AIHA. Computed tomography (CT) scan and positron-emission tomography (PET) scan sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The association between HL and AIHA is well known . Although rare, the literature reports few cases of patients presenting an authentic AIHA associated with HL, generally of nodular sclerosing or mixed cellularity subtypes . However, HL‐associated AIHA typically precedes disease diagnosis or occurs in progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…The association between HL and AIHA is well known . Although rare, the literature reports few cases of patients presenting an authentic AIHA associated with HL, generally of nodular sclerosing or mixed cellularity subtypes . However, HL‐associated AIHA typically precedes disease diagnosis or occurs in progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this finding, one can suggest that T-PLL has temporally preceded the development of wAIHA. ( 2) It is well-reported in the literature that 50% of cases of AIHA are due to the presence of a secondary underlying cause [15]. However, our extensive workup did not reveal evidence of any secondary cause except T-PLL.…”
Section: Discussionmentioning
confidence: 56%
“…Whether it is true for all such cases needs the addition of similar cases in the literature. Moreover, some malignancy-related AIHA disappears when underlying malignancy is treated [15]. Whether this is true for T-PLL-associated AIHA remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, a study with 492 patients showed that the incidence of AIHA associated with Hodgkin’s disease was 0.2% 8 and the data from the United States was 3–4% 9 , which usually occurs in stage III and IV of nodular sclerosis and mixed cell type 10,11 . We found that only one patient had stage IV Hodgkin’s disease, and the pathological pattern showed a combined cell type.…”
Section: Discussionmentioning
confidence: 99%